The Method of Teaching Listening Comprehension in the Third Cycle of Primary Education - guemmaz, djamila; khalafe, messuda (El Omda in Linguistics and Discourse Analysis, 2022)
Operative Under standing is one of the innovatives linguistic activities in the second generation s curricula .It is based on Listening. Where the text goes through two phases that are : blondes of the text that consists on the delivery of the text on the ears of learnes, conversing with them, summarizing them and conclu ding a value from it and text dramatization by transforming the text s events to Play that is performed by the learners. In that way they creat a cognitive level.